The Influence Of Experiential Marketing (Sense Marketing, Feel Marketing, Think Marketing, Act Marketing) Against The Quality Of The College Of Religious Islam Negeri (PTKIN) In East Java Indonesia - Haryanti, Nik; Prim Masrokan Mutohar; Mujamil Qomar; Asrop Syafi’i (Publisher Cv. Inara, 2022)
The purpose of this study is to analyze the influence of the sense of marketing, feel marketing, think marketing, act arketing and relate marketing to High quality Religious Islam Negeri (PTKIN). This type of Research using mixed methods (mixed method). The population in this study is 1.304 personnel. Sample research are 200 staffs. data collection techniques are questionnaires, interviews, observation and documentation. The data analysis technique used is quantitative analysis by using SEM AMOS. The results of the research indicate that there is influence of sense marketing, feel marketing, think marketing is the act of marketing and relate marketing to High quality Religious Islam Negeri (PTKIN) in IAIN Tulungagung and UIN Malang.